The Influence of Security and Quality Mobile Banking Services on Customer Satisfaction and the Impact on Loyalty Private Bank Customers - Sugijanto, Antonius William; Efrata, Tommy Christian; Christian, Sonata (International Business Management - Universitas Ciputra, 2025)
This study aims to examine the impact of mobile banking security and service quality on customer loyalty, with customer satisfaction as a mediating variable. A quantitative research approach was employed, utilizing a non-probability sampling technique. Specifically, purposive sampling was used to select respondents based on predetermined criteria. The study involved 152 respondents, all BCA bank customers in Surabaya who actively use MyBCA. Data were collected through questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both mobile banking security quality and service quality positively and significantly influence customer loyalty, with customer satisfaction playing a key mediating role.